Leibniz on Slavery and the Ownership of Human Beings - Julia Jorati (Journal of Modern Philosophy)
Leibniz puts forward an intriguing argument against the moral permissibility of chattel slavery in a text from 1703. This argument has three independent layers or sub-arguments. The first is that slavery violates natural rights. The second is that moral laws such as the principles of equity and piety oppose slavery, or at least severely limit the permissible actions toward slaves. The third and final layer is that slavery can at most be justified if the slave is permanently incapable of conducting herself well. Yet, it is very doubtful that any actual human beings satisfy that description. This paper analyzes and evaluates Leibniz’s argument, which scholars have so far largely neglected. Even though some elements of the argument are not original to Leibniz, it is of considerable importance for the scholarship of early modern philosophy: it sheds light on Leibniz’s views not only on the moral status of slavery itself, but also on moral rights and obligations more generally.